Industry Financial Ratios - Application Of Factor Analysis In Malaysian Industrial Sector - Zulkifli, Nor Aizura (2010)
The purpose of this study is to identify the most important indicators that contribute to Malaysian industrial sector and to analyze the financial trend from year 2000 to 2008. Tujuan kajian ini adalah untuk mengenal pasti penunjukpenunjuk paling penting yang menyumbang untuk sektor perindustrian Malaysia dan untuk menganalisa aliran kewangan dari tahun 2000 hingga 2008.